SISTEM INFOMASI SEKOLAH DAN DATA ALUMNI DI SMK NEGERI 2 TEMBILAHAN - Ayu Sri Rahinda; Fitri Yunita; Muh. Rasyid Ridha; Usman Usman (JURNAL PERANGKAT LUNAK, 2024)
The thesis, entitled "School Information System and Alumni Data at SMK Negeri 2 Tembilahan", was made against the background of the absence of a school information system that stores alumni data at SMK Negeri 2 Tembilaha, data is still stored in the form of archival documents and the unavailability of school information about alumni data that can be accessed online. In making this system using the waterfall method with PIECES analysis, the system design uses UML modeling. The results obtained are solutions to the difficulty of the community in finding school information and the difficulty of alumni in finding alumni data.